The Impact of AI on Trends, Design, and Consumer Behavior - Yazdani, Ali; Darbani, Shoaleh (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore the multifaceted impact of AI on trends, design innovations, and shifts in consumer behavior. It seeks to identify the main themes that characterize AI's influence across these domains, providing insights into how AI is reshaping consumer interactions, design practices, and market dynamics. Utilizing a qualitative research approach, the study conducted semi-structured interviews with 27 participants from various professional backgrounds, including digital design, AI research, trend analysis, consumer psychology, and product development. Thematic analysis was employed to distill the data into coherent themes, categories, and concepts. The analysis revealed three main themes: Trends in AI Adoption and Impact, Design Innovations Enabled by AI, and Shifts in Consumer Behavior due to AI. Each theme comprises several categories with specific concepts that highlight AI's role in personalization, automation, ethical practices, sustainable solutions, user experience design, interactive and adaptive design, purchasing behavior, engagement, and consumer trust. These findings illuminate the comprehensive influence of AI, from enhancing operational efficiencies and ethical considerations to reshaping consumer purchasing decisions and engagement strategies. AI's integration into consumer markets, design processes, and societal trends presents both opportunities and challenges. This study underscores the importance of ethical considerations, consumer trust, and personalized experiences in leveraging AI's potential. By navigating these elements thoughtfully, AI can contribute positively to consumer behavior, design innovation, and market trends, fostering a more engaged, efficient, and ethically conscious future.